Sublimacja płaskiej ścianki pod wpływem promieniowania gazu ogrzanego silną falą uderzeniową - Kopystyński, J. (Engineering Transactions, 1969)
In this paper, theoretical consideration is given to a certain model of the interaction of a strong shock wave, propagating in a perfect gas, with the surface of a solid body (wall). It is assumed that the incident or reflected shock wave interacts with the wall means of radiation energy transfer. In the calculations concerning the approach of the wave to the wall two different models of radiation transport were applied. The conditions of sublimation formation were discussed qualitatively (in the full range of the variation of time) and quantitatively (only for the case in which the sublimation occurs just after the reflection of the wave). The equation determining the moment of the beginning of sublimation is also given. It is found that if in a concrete case the sublimation does not start before the reflection of the wave, then the radiation emitted by the incident wave can be neglected in comparison with the radiation from the gas heated by the reflected wave. Also given is numerical example of the solution of the equation of thermal conductivity in the case of a sublimating wall, and the rate of sublimation is determined.